Morphology and phase state of PM2.5 in urban and coastal-rural areas during summer - Gaikwad, Sanjit; Kim, Daeun; Jeong, Rani; Lee, Ji Yi; Lee, Kwangyul; Ahn, Junyoung; Jang, Kyoung-Soon; Kim, Changhyuk; Song, Mijung (Frontiers in Environmental Science, 2023)
The morphology and phase state are critical physical properties of aerosol particles. However, studies related to the analysis of these properties primarily focus on laboratory experiments, and studies on real aerosol particles are limited. Herein, fine particulate matter (PM2.5) filter samples were obtained to investigate and compare the morphology and phase state of ambient aerosol particles in South Korea. The PM2.5 samples were collected in the summer of June 2021 from two different environments: Seoul (urban) and Seosan (coastal-rural). Optical microscopy was combined with the poke-and-flow technique to determine the morphology and phase state of the PM2.5 as a function of relative humidity (RH) at 293 ± 1 K. At both sites, the PM2.5 droplets, which were extracted in purified water, showed a multiphase nature that was dependent on the RH and chemical composition. Based on the results and ambient average RH in Seoul, most of the PM2.5 was observed in a liquid state on polluted days under an inorganic-dominant condition, but in a semisolid state on clean days under an organic carbon-rich condition. In Seosan, the PM2.5 predominantly existed in a liquid state, due to the high RH caused by proximity to the Yellow Sea. Our study provides fundamental physical properties of PM2.5 for both urban and coastal-rural environments. The results have strong applications for atmospheric chemistry and predicting particle size distributions.